Determining the behavior of a glass panel under heating conditions during a fire - Nekora, Valeriia; Pozdieiev, Serhii; Nekora, Olga; Fedchenko, Svitlana; Nizhnyk, Vadym; Novhorodchenko, Alina; Shnal, Taras (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the processes of heating and destruction of glazing in translucent elements of fencing structures. The paper provides data on the computer simulation of a glass panel behavior when it is heated on one side under the conditions of exposure to the standard fire temperature regime. With the help of computer simulation of a glass panel under conditions of thermal influence, the process of heat transfer was reproduced based on the non-stationary heat conduction equation. The stress-strain state of the glass panel was considered using the finite element method. The thermal effect was combined with the mechanical load due to the excess pressure that can occur in the room where the fire originates and develops. To study the propagation of cracks in glass, the strength criterion according to the Johnson-Holmquist model was applied. As a result of computer simulation based on a mathematical model, data were obtained on the dynamics of the formation and propagation of cracks in a glass panel under conditions of heating according to the standard fire temperature regime. It is shown that the glass panel is destroyed through the formation of a system of branched cracks, which is confirmed by empirical experience. The destruction of the glass panel was associated with the onset of the limit state of loss of integrity, and its fire resistance limit was registered based on this attribute. In the work, a comparative analysis of the obtained data with the findings from experimental studies has been carried out. As a result of the comparative analysis, it is shown that the results are adequate since their relative error is on average no more than 8 %, and the F-criterion of adequacy at the significance level of 0.05 does not exceed the tabular value. Based on the results, the possibility of its application for a reliable analysis of the fire resistance of enclosing elements in building structures has been proven